{"title":"模逻辑","authors":"M. El Alaoui","doi":"10.1201/9781003168416-2-2","DOIUrl":null,"url":null,"abstract":"Solution. A5 = ♦A ⊃ ♦A = ¬ ¬A ⊃ ¬ ¬A. We show that F 6|= ¬Ki¬F ⊃ Ki¬Ki¬F for some formula F if and only if F 6|= ¬KiG ⊃ Ki¬KiG for some formula G. Let F 6|= ¬Ki¬F ⊃ Ki¬Ki¬F for some formula F . That is, (M, w) 6|= ¬Ki¬F ⊃ Ki¬Ki¬F for some world w in some interpretationM based on F . Choosing G = ¬F we obtain (M, w) 6|= ¬KiG ⊃ Ki¬KiG and therefore also F 6|= ¬KiG ⊃ Ki¬KiG. Conversely, let F 6|= ¬KiG ⊃ Ki¬KiG for some formula G. That is, (M, w) 6|= ¬KiG ⊃ Ki¬KiG for some world w in some interpretation M based on F . Furthermore we have (M, w) 6|= ¬Ki¬¬G ⊃ Ki¬Ki¬¬G. Choosing F = ¬G we obtain (M, w) 6|= ¬Ki¬F ⊃ Ki¬Ki¬F and therefore also F 6|= ¬Ki¬F ⊃ Ki¬Ki¬F .","PeriodicalId":137534,"journal":{"name":"Fuzzy TOPSIS","volume":"1 1","pages":"0"},"PeriodicalIF":0.0000,"publicationDate":"1900-01-01","publicationTypes":"Journal Article","fieldsOfStudy":null,"isOpenAccess":false,"openAccessPdf":"","citationCount":"6","resultStr":"{\"title\":\"Nonclassical Logics\",\"authors\":\"M. El Alaoui\",\"doi\":\"10.1201/9781003168416-2-2\",\"DOIUrl\":null,\"url\":null,\"abstract\":\"Solution. A5 = ♦A ⊃ ♦A = ¬ ¬A ⊃ ¬ ¬A. We show that F 6|= ¬Ki¬F ⊃ Ki¬Ki¬F for some formula F if and only if F 6|= ¬KiG ⊃ Ki¬KiG for some formula G. Let F 6|= ¬Ki¬F ⊃ Ki¬Ki¬F for some formula F . That is, (M, w) 6|= ¬Ki¬F ⊃ Ki¬Ki¬F for some world w in some interpretationM based on F . Choosing G = ¬F we obtain (M, w) 6|= ¬KiG ⊃ Ki¬KiG and therefore also F 6|= ¬KiG ⊃ Ki¬KiG. Conversely, let F 6|= ¬KiG ⊃ Ki¬KiG for some formula G. That is, (M, w) 6|= ¬KiG ⊃ Ki¬KiG for some world w in some interpretation M based on F . Furthermore we have (M, w) 6|= ¬Ki¬¬G ⊃ Ki¬Ki¬¬G. Choosing F = ¬G we obtain (M, w) 6|= ¬Ki¬F ⊃ Ki¬Ki¬F and therefore also F 6|= ¬Ki¬F ⊃ Ki¬Ki¬F .\",\"PeriodicalId\":137534,\"journal\":{\"name\":\"Fuzzy TOPSIS\",\"volume\":\"1 1\",\"pages\":\"0\"},\"PeriodicalIF\":0.0000,\"publicationDate\":\"1900-01-01\",\"publicationTypes\":\"Journal Article\",\"fieldsOfStudy\":null,\"isOpenAccess\":false,\"openAccessPdf\":\"\",\"citationCount\":\"6\",\"resultStr\":null,\"platform\":\"Semanticscholar\",\"paperid\":null,\"PeriodicalName\":\"Fuzzy TOPSIS\",\"FirstCategoryId\":\"1085\",\"ListUrlMain\":\"https://doi.org/10.1201/9781003168416-2-2\",\"RegionNum\":0,\"RegionCategory\":null,\"ArticlePicture\":[],\"TitleCN\":null,\"AbstractTextCN\":null,\"PMCID\":null,\"EPubDate\":\"\",\"PubModel\":\"\",\"JCR\":\"\",\"JCRName\":\"\",\"Score\":null,\"Total\":0}","platform":"Semanticscholar","paperid":null,"PeriodicalName":"Fuzzy TOPSIS","FirstCategoryId":"1085","ListUrlMain":"https://doi.org/10.1201/9781003168416-2-2","RegionNum":0,"RegionCategory":null,"ArticlePicture":[],"TitleCN":null,"AbstractTextCN":null,"PMCID":null,"EPubDate":"","PubModel":"","JCR":"","JCRName":"","Score":null,"Total":0}
Solution. A5 = ♦A ⊃ ♦A = ¬ ¬A ⊃ ¬ ¬A. We show that F 6|= ¬Ki¬F ⊃ Ki¬Ki¬F for some formula F if and only if F 6|= ¬KiG ⊃ Ki¬KiG for some formula G. Let F 6|= ¬Ki¬F ⊃ Ki¬Ki¬F for some formula F . That is, (M, w) 6|= ¬Ki¬F ⊃ Ki¬Ki¬F for some world w in some interpretationM based on F . Choosing G = ¬F we obtain (M, w) 6|= ¬KiG ⊃ Ki¬KiG and therefore also F 6|= ¬KiG ⊃ Ki¬KiG. Conversely, let F 6|= ¬KiG ⊃ Ki¬KiG for some formula G. That is, (M, w) 6|= ¬KiG ⊃ Ki¬KiG for some world w in some interpretation M based on F . Furthermore we have (M, w) 6|= ¬Ki¬¬G ⊃ Ki¬Ki¬¬G. Choosing F = ¬G we obtain (M, w) 6|= ¬Ki¬F ⊃ Ki¬Ki¬F and therefore also F 6|= ¬Ki¬F ⊃ Ki¬Ki¬F .